Kit's wilderness - Almond, David, 1951- (New York : Dell Laurel-Leaf, 2001)
Thirteen-year-old Kit goes to live with his grandfather in the decaying coal mining town of Stoneygate, England, and finds both the old man and the town haunted by ghosts of the past.
Keywords: Coal mines and mining -- Fiction; Grandfathers -- Fiction; Old age -- Fiction; England -- Fiction; Printz Medal; Ghost stories